nidantasnu

Answered

2022-07-05

Consider the following sum:
$S\left(n\right)=\sum _{k=0}^{\mathrm{\infty }}\frac{\left(\genfrac{}{}{0}{}{2k+n}{k}\right)}{2k+n}\frac{1}{{2}^{2k}};n=0,1,2,3,...$

Answer & Explanation

Karla Hull

Expert

2022-07-06Added 20 answers

The sum at hand is a hypergeometric series. Let
${c}_{k}=\frac{1}{n+2k}\left(\genfrac{}{}{0}{}{n+2k}{k}\right)\frac{1}{{2}^{2k}}=\frac{\left(n-1+2k\right)!}{k!\left(n+k\right)!}\frac{1}{{4}^{k}}$
Indeed, the hypergeometric certificate is:
$\frac{{c}_{k+1}}{{c}_{k}}=\frac{1}{4}\frac{\left(n+2k\right)\left(n+2k+1\right)}{\left(n+1+k\right)\left(k+1\right)}$
Meaning that
$\sum _{k=0}^{\mathrm{\infty }}{c}_{k}={c}_{0}\sum _{k=0}^{\mathrm{\infty }}\frac{{\left(n/2\right)}_{k}{\left(n/2+1/2\right)}_{k}}{\left(n+1{\right)}_{k}}\frac{1}{k!}=\frac{1}{n}\cdot {}_{2}{F}_{1}\left(\frac{n}{2},\frac{n+1}{2};n+1;1\right)$
where $\left(a{\right)}_{k}$ denotes Pochhammer symbol. Using Gauss's theorem, applicable for $\mathrm{\Re }\left(c-a-b\right)>0$
${}_{2}{F}_{1}\left(a,b;c;1\right)=\frac{\mathrm{\Gamma }\left(c\right)\mathrm{\Gamma }\left(c-a-b\right)}{\mathrm{\Gamma }\left(c-a\right)\mathrm{\Gamma }\left(c-b\right)}$
we have
$\sum _{k=0}^{\mathrm{\infty }}{c}_{k}=\frac{1}{n}\frac{\mathrm{\Gamma }\left(n+1\right)\mathrm{\Gamma }\left(\frac{1}{2}\right)}{\mathrm{\Gamma }\left(\frac{n}{2}+1\right)\mathrm{\Gamma }\left(\frac{n+1}{2}\right)}\stackrel{\text{duplication}}{=}\frac{1}{n}\frac{{2}^{n}{\pi }^{-1/2}\mathrm{\Gamma }\left(\frac{n+1}{2}\right)\mathrm{\Gamma }\left(\frac{n}{2}\right)\mathrm{\Gamma }\left(\frac{1}{2}\right)}{\mathrm{\Gamma }\left(\frac{n}{2}\right)\mathrm{\Gamma }\left(\frac{n+1}{2}\right)}=\frac{{2}^{n}}{n}$
Since $\mathrm{\Gamma }\left(1/2\right)=\sqrt{\pi }$

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?